Feeding Practices among Human Immunodeficiency Virus-Exposed Infants in Ethiopia: Systematic Review and Meta-Analysis. (10th March 2021) - Temesgen, Habtamu; Negesse, Ayenew; Getaneh, Temesgen; Bazezew, Yibelu; Haile, Dessalegn; Woyraw, Wubetu; Desta, Melaku; Aderaw Alamneh, Alehegn
Abstract : Background . Infant and young child feeding in the context of human immunodeficiency virus- (HIV-) infected mothers has significant challenges due to the risk of transmission of the virus via breastfeeding. In Ethiopia, a number of independent studies have been conducted to assess the feeding practice of HIV-exposed infants. But, there is no concrete evidence to show the national figure in Ethiopia. Hence, this review and meta-analysis aims to estimate the pooled prevalence of feeding practices among HIV exposed infants in Ethiopia. Methods . The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was followed. Articles were searched through search engines in PubMed, Cochrane Library, Google Scholar, and direct Google search. Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument adapted for cross-sectional study design was used for quality assessment. The random effects model was used to estimate the pooled prevalence of infant feeding practices. Heterogeneity and publication bias were assessed. Trim and fill analysis was performed. Additionally, meta-regression was also performed. Results . In this review, a total of 26, 22, and 22 studies and 7413, 6224, and 6222 study participants for exclusive breastfeeding, replacement feeding, and mixed feelings were included, respectively. The overall pooled prevalence of exclusive breastfeeding, replacement feeding, and mixed feeding of HIV exposed infant was 63.99 % (95% Confidence Interval (CI): 52.32, 75.66), 16.13% (95% CI: 11.92, 20.32), and 20.95% (95% CI: 11.35, 30.58)) in Ethiopia, respectively. Conclusion and Recommendations . In Ethiopia, almost three in five HIV-exposed infants were exclusively breastfed. But still, mixed feeding during the period of first 6 months was practiced in almost one-fifth of the exposed infants in Ethiopia. Additionally, replacement feeding was also practiced even though not recommended for developing countries. Therefore, the government of Ethiopia should strengthen the health institutions to implement the existing infant feeding strategies and guidelines to increase exclusive breastfeeding for the first 6 months and to avoid mixed feeding during the periods of six months.